2004
DOI: 10.1191/0961203304lu491oa
|View full text |Cite
|
Sign up to set email alerts
|

High-dose immunosuppression with autologous stem cell transplantation in severe refractory systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an immune-mediated disease that is responsive to suppression or modulation of the immune system. Patients with SLE who experience persistent multiorgan dysfunction, despite standard doses of intravenous cyclophosphamide (Cy), represent a subset of patients at high risk of early death. We investigated the efficacy and toxicity of high-dose immunosuppression and autologous hematopoietic stem cell transplantation (SCT) to treat such patients. Six patients (all female, age 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
1
27
0
4
Order By: Relevance
“…A number of reports have appeared in the literature showing that this technique has potential benefit in severe autoimmune disease [70], in PAN [85] and in SLE [59,68]. Such a step is not going to be taken lightly but none-the-less may have a role when there is no alternative approach available.…”
Section: Immunoablation and Autologous Stem Cell Transplantationmentioning
confidence: 97%
“…A number of reports have appeared in the literature showing that this technique has potential benefit in severe autoimmune disease [70], in PAN [85] and in SLE [59,68]. Such a step is not going to be taken lightly but none-the-less may have a role when there is no alternative approach available.…”
Section: Immunoablation and Autologous Stem Cell Transplantationmentioning
confidence: 97%
“…Transplantation is able to change the behavior of severe diseases, making them more benign and responsive to therapy. It has been suggested that the reported higher rates of mortality in Brazil and other countries (25) can be controlled by appropriate patient selection, the choice of a less aggressive conditioning regime and the acquisition of more experience in managing specific complications associated with the procedure (21).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Por outro lado, o grupo de Zhengzhou transplantou 18 pacientes, observando-se 12 remissões completas, três parciais, três falhas terapêuticas e duas recaídas, mas nenhum óbito (33) e o grupo de Shangai relatou TCTH bem sucedido em duas crianças (de cinco e sete anos) portadoras de LES (34) . Na experiência russa, dentre seis pacientes com LES condicionados com BEAM+ATG, ocorreram três óbitos por complicações do transplante, duas remissões completas e uma remissão parcial (35) .…”
Section: Bases Científicas Para O Tratamento De Doenças Auto-imunes Cunclassified